Stock assessment of the Indian squid Loligo duvauceli Orbigny - Meiyappan, M M; Srinath, M; Nair, K Prabhakaran; Rao, K Satyanarayana; Sarvesan, R; Rao, G Syda; Mohamed, K S; Vidyasagar, Kuber; Sundaram, K S; Lipton, A P; Natarajan, P; Radhakrishnan, G; et al. (Indian Journal of Fisheries, 2011)
The present status of the fishery, biology and stock assessment of the India squid Loligo duvauceliOrbigny was studied, based on the data collected at different centres on both the coasts of India for1979-1989. The production had increased by over 280% in 3 states on the west coast, viz. Kerala,Maharashtra and Gujarat. These states accounted for about 80% of the all-India squid production(23,941 t in 1989). Trawl is the main gear, taking 86% of the total squid landings. The fishing effortand squid catch on the east coast was comparatively more in the third quarter. On the west coast thefirst and fourth quartÂ«^ were the most productive. The natural mortality rates calculated based ondifferent levels of M/K values (1.5, 2, 2.5 and 3) showed that they ranged from 1.35 to 2.7 for malesand from 1.95 to 3.9 tor females on the east coast; from 1.2 to 2.4 for males and from 1.65 to 3.3 forfemales on the west coast. On both the coasts the values for females were higher than for males. Themaximum fishing mortality (1.2 - 4.3) under different M/K values for males was at the size of 85 mm,and for females (5.8 - 6.7) at 175 mm on the east coast. For the west coast males the maximum fishingmortality (3.3 - 4.3) was at the size of 230 mm and for females (2.3 - 3.8) at 130 mm. The standingstock of males was higher than that of females on the east coast, with a reverse order on the west coast.The MSY and mean biomass at different M/K levels were also estimated for males and females separatelyfor each coast. The present level of exploitation was at the optimum level on both the coasts.